Flexible calorimetric flow sensor with unprecedented sensitivity and directional resolution for multiple flight parameter detection - Gong, Zheng; Di, Weicheng; Jiang, Yonggang; Dong, Zihao; Yang, Zhen; Ye, Hong; Zhang, Hengrui; Liu, Haoji; Wei, Zixing; Tu, Zhan; Li, Daochun; Xiang, Jinwu; et al. (Nature communications, 2024)
The accurate perception of multiple flight parameters, such as the angle of attack, angle of sideslip, and airflow velocity, is essential for the flight control of micro air vehicles, which conventionally rely on arrays of pressure or airflow velocity sensors. Here, we present the estimation of multiple flight parameters using a single flexible calorimetric flow sensor featuring a sophisticated structural design with a suspended array of highly sensitive vanadium oxide thermistors. The proposed sensor achieves an unprecedented velocity resolution of 0.11 mm·s −1 and angular resolution of 0.1°. By attaching the sensor to a wing model, the angles of attack and slip were estimated simultaneously. The triaxial flight velocities and wing vibrations can also be estimated by sensing the relative airflow velocity due to its high sensitivity and fast response. Overall, the proposed sensor has many promising applications in weak airflow sensing and flight control of micro air vehicles. Accurate perception of flight parameters is critical for flight control of micro air vehicles. Here, authors present a flexible calorimetric flow sensor with vanadium oxide thermistor arrays for flight parameters estimation, such as angle of attack and sideslip, flight velocity, and wing vibration.